A multilayer microperforated panel prototype for broadband sound absorption at low frequencies. (March 2019) - Bucciarelli, F.; Malfense Fierro, G.P.; Meo, M.
Abstract: Microperforated panel (MPP) absorbers are one of the most promising alternatives to porous sound absorbing materials. However, these structures cannot achieve high and broadband absorption at low frequencies. To be effective, once defined the material properties the geometrical parameters of the absorber need to be optimized to match the prescribed absorption level. This paper presents a multiple layer MPP absorber with a high sound absorption coefficient and broadband absorption at low frequencies. An electro-acoustical equivalent circuit model was used for a parametric analysis to study the relationships between the absorption mechanism and the absorbers geometrical parameters in the proposed multilayer MPP. A prototype of this absorber was machined and tested in an impedance tube test ring and the experimental acoustical properties in terms of absorption coefficient were extracted using the transfer function method. It was demonstrated that the five-layer MPP absorber was capable of guaranteeing a high absorption (constantly over 90%) in a frequency range from 400 to 2000 Hz. The results indicate that the proposed multilayer MPP absorber provides a good alternative for sound absorption applications.